1994
DOI: 10.1111/j.1751-1097.1994.tb05037.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Photochemical Properties of Curcumin

Abstract: Curcumin, bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione, is a natural yellow-orange dye derived from the rhizome of Curcuma longa, an East Indian plant. In order to understand the photobiology of curcumin better we have studied the spectral and photochemical properties of both curcumin and 4-(4-hydroxy-3-methoxy-phenyl)-3-buten-2-one (hC, half curcumin) in different solvents. In toluene, the absorption spectrum of curcumin contains some structure, which disappears in more polar solvents, e.g. ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
284
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(319 citation statements)
references
References 25 publications
(3 reference statements)
25
284
0
10
Order By: Relevance
“…37,38 A comparison between the UV-vis absorption and emission spectra of curcumin in micelles with those in a number of organic solvents and water provides valuable insights. The UV-vis absorption spectra of curcumin in the TX-100 and DTAB micelles resemble those of curcumin in aprotic solvents, including chloroform and toluene, 23,39 suggesting similarities between the environments. However, the emission spectra of curcumin in these micelles are red-shifted compared to those in the aprotic solvents, potentially due to interactions with water molecules at the interface and within the micelle, [40][41][42][43][44] as will be discussed further in a later section.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 92%
“…37,38 A comparison between the UV-vis absorption and emission spectra of curcumin in micelles with those in a number of organic solvents and water provides valuable insights. The UV-vis absorption spectra of curcumin in the TX-100 and DTAB micelles resemble those of curcumin in aprotic solvents, including chloroform and toluene, 23,39 suggesting similarities between the environments. However, the emission spectra of curcumin in these micelles are red-shifted compared to those in the aprotic solvents, potentially due to interactions with water molecules at the interface and within the micelle, [40][41][42][43][44] as will be discussed further in a later section.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 92%
“…The use of fluences higher than 18 J/cm 2 did not improve the effectiveness of PDT for inactivating the Candida species. This could be as a result of the CUR photobleaching which leads to photodegradation of the PS solution and decreases in reactive oxygen species production [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of investigations have suggested that CUR exhibits potential therapeutic applications that may be enhanced by combination with light, as it displays a high light absorption in the visible spectral region, around 400-500 nm [23][24][25][26]. Recently, this natural compound has been shown to possess phototoxic potential against yeast cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…By changing the properties of the solvent, such as polarity, the spectroscopic properties may vary dramatically [22,23]. In addition, curcumin can be synthetized with metallic ions in its structure, also changing its spectroscopic properties [24].…”
Section: Introductionmentioning
confidence: 99%